Strategic behavior of small firms and business group affiliation - Ćwik, Krzysztof (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
One of the criteria differentiating small firms is the fact of being the part of a business group. This feature seems to be quite significant in the context of research on entities from this size class of enterprises. The article presents the results of the study on the strategic behavior of companies of this size class. The results showed quite significant differences depending on whether the study objects were subsidiaries or were capital-independent. These differences should become a reason to consider the application of the criterion of enterprise independence in the selection of a research sample in the empirical verification of hypotheses posed in management and quality sciences.